A qualitative study of the needs of older adults with intellectual disabilities. Issue 6 (14th June 2021) - McCausland, Darragh; Guerin, Suzanne; Tyrrell, Janette; Donohoe, Clare; O'Donoghue, Isabelle; Dodd, Philip
Abstract: Background: Research indicates that adults with intellectual disabilities are living longer. However, there is limited research on how this affects health and care needs. Objective: The present study aimed to examine the health and social care needs of older adults with intellectual disabilities in Ireland using multiple informants. Methods: Data were gathered from a sample of 20 adults aged 50 years or older (Mean = 59.1, SD = 5.9, range = 50–72; 11 female). The sample included individuals with mild ( n = 7), moderate ( n = 10) and severe/profound ( n = 3) intellectual disabilities. Additional data from keyworkers ( n = 19) and family carers ( n = 15) provided a more complete understanding of needs. Results: Results revealed some areas of agreement and difference between adults with intellectual disability and their carers regarding the social care, employment, retirement, physical and mental health needs of this population. Conclusions: The findings of this study have potential implications for the provision of high‐quality services for older adults with intellectual disabilities.